Coaching the mind: Practical guidelines for using soft skills to prepare athletes for competitive events - Waskiewicz, Z. (Journal of Biathlon Coaching, 2025)
In the final days before competition, athletes often encounter escalating psychological demands. Anticipation, internal pressure and performance anxiety may compromise focus and emotional stability. While tactical plans and physical preparation remain essential, coaches are increasingly recognized as relational leaders - individuals who shape the psychological environment in which performance unfolds. Côté and Gilbert (2009) emphasize that effective coaching draws both from technical knowledge and from the coach`s interpersonal and intrapersonal capacities. These include the ability to manage emotional tone, build trust and adapt communication each athlete`s context. Especially under pressure, such relational skills enhance athlete competence, confidence and connection - the foundation of readiness in competitive sport.